Lincoln Center for the Performing Arts - Martin, Ralph G. 1920-2013 (Englewood Cliffs (N.J.) Prentice-Hall, 1971)
The exciting drama of New York's Lincoln Center for the Performing Arts unfolds in this definitive and lavishly illustrated book. From the conception of a new idea, through opening nights and recent achievements in theater, ballet, opera, and music, this is the story of Lincoln Center's birth and development, its role as a vital community force, its pageantry, and it's promise.
Acknowledgments -- Introduction -- The New York Philharmonic -- The New York State Theater -- The Repertory Theater -- The Library & Museum of the Performing Arts -- The Metropolitan Opera -- The Juilliard School -- Lincoln Center -- Index.
Keywords: Lincoln Center for the Performing Arts; Cultural history; Institution; Education; New York City (USA)